Prophet song - Lynch, Paul, 1977- (London : Oneworld, 2023)
"On a dark, wet evening in Dublin, scientist and mother-of-four Eilish Stack answers her front door to find two officers from Ireland's newly formed secret police on her step. They have arrived to interrogate her husband, a trade unionist. Ireland is falling apart, caught in the grip of a government turning toward tyranny. As the life she knows and the ones she loves disappear before her eyes, Eilish must contend with the dystopian logic of her new, unraveling country. How far will she go to save her family? And what-or who-is she willing to leave behind? Exhilarating, terrifying, and surprisingly intimate, Prophet Song offers a shocking vision of a country at war and a deeply human portrait of a mother's fight to hold her family together"--
AAL
R K Corporation
Booker Prize for Fiction, 2023.
Keywords: English fiction; Dystopian fiction; Novels